A rare case of postpartum cerebral venous thrombosis and hemmorhagic infarct - Jamwal, Sonal; Kaushal, Drishti; Rattan, Arushi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cerebral venous thrombosis (CVT) is a rare but serious complication that can occur during pregnancy and the postpartum period. This case reports discusses a unique instance of postpartum CVT complicated by hemorrhagic infarct in a patient from Himachal Pradesh. A case of a 26-year-old woman, para 2, unbooked patient with normal vaginal delivery at home, presented on 10th postpartum day with complaint of vomiting, headache, left hemiplegia and seizures, initially misdiagnosed as eclampsia, underwent CT, revealed significant sigmoid sinus thrombosis with haemorrhagic infarction. The patient underwent left fronto-temporoparietal decompressive hemicranectomy with duroplasty at PGIMER Chandigarh followed by tracheostomy. The patient was under antibiotic treatment, seizure prophylaxis, anticoagulation therapy, resulting in substantial clinical improvement. This case emphasizes the necessity of maintaining a high index of suspicion for CVT in postpartum women displaying neurological symptoms. Misdiagnosis can impede timely intervention, highlighting the need for access to advanced imaging and multidisciplinary approach. Increasing awareness and training for healthcare providers are essential for timely diagnosis. Also, the importance of hospital delivery. The management of this case illustrates the importance of regular antenatal checkup, hospital delivery, early recognition of CVT in the postpartum population. Enhancing diagnostic resources and treatment strategies, particularly in resource limited settings, can significantly improve maternal health outcomes and reduce morbidity and mortality. The possibility of cerebral vein thrombosis should be considered in all women with brain dysfunction during the puerperium.